2020
DOI: 10.1074/jbc.ra119.011083
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry–based selectivity profiling identifies a highly selective inhibitor of the kinase MELK that delays mitotic entry in cancer cells

Abstract: The maternal embryonic leucine zipper kinase (MELK) has been implicated in the regulation of cancer cell proliferation. RNAi-mediated MELK depletion impairs growth and causes G2/M arrest in numerous cancers, but the mechanisms underlying these effects are poorly understood. Furthermore, the MELK inhibitor OTSSP167 has recently been shown to have poor selectivity for MELK, complicating the use of this inhibitor as a tool compound to investigate MELK function. Here, using a cell-based proteomics technique called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Further, the binding affinity of OTS for MELK is lower than its binding affinity for 15 other protein kinases (see supporting material of the Klaeger et al study (13) for quantifications). Using a similar MS-based selectivity-profiling method (MIB/MS), our group recently confirmed the low specificity of OTS (14). We showed that 12 protein kinases were inhibited more than MELK by 1 M OTS, and 52 kinases (of 235 that were quantified) were inhibited Ն75% at this concentration.…”
Section: Commentary On the Melk Requirement Controversymentioning
confidence: 85%
See 4 more Smart Citations
“…Further, the binding affinity of OTS for MELK is lower than its binding affinity for 15 other protein kinases (see supporting material of the Klaeger et al study (13) for quantifications). Using a similar MS-based selectivity-profiling method (MIB/MS), our group recently confirmed the low specificity of OTS (14). We showed that 12 protein kinases were inhibited more than MELK by 1 M OTS, and 52 kinases (of 235 that were quantified) were inhibited Ն75% at this concentration.…”
Section: Commentary On the Melk Requirement Controversymentioning
confidence: 85%
“…Because of its status as the leading MELK inhibitor, OTS has been used in most functional studies of MELK since its development. It has recently been definitively demonstrated that OTS has extremely poor selectivity for MELK (13)(14)(15)(16)), yet unfortunately, it is still regularly used as a tool compound to investigate MELK function.…”
Section: A Brief Overview Of Melk: From Discovery To Controversymentioning
confidence: 99%
See 3 more Smart Citations